Word association research and the L2 lexicon. (July 2020) - Fitzpatrick, Tess; Thwaites, Peter
Abstract: Since its modern inception in the late nineteenth century, research on word associations has developed into a large and diverse area of study, including work with both applied linguistic and psycholinguistic orientations. However, despite significant recent interest in the use of word association to investigate second language (L2) vocabulary knowledge and testing, there has until now been no systematic attempt to review the wider word association research tradition for the benefit of L2-oriented researchers and practitioners. This paper seeks to address this, drawing together linguistic research from the past 150 years, with a focus on research published since 2000. We evaluate the current state of L2 word association research, before identifying methodological and theoretical themes from a broader range of disciplinary approaches. Emerging from this, new paradigms are identified which have potential to catalyse a new phase of work for second language word association scholars, and which indicate priority foci for future work.